2022
DOI: 10.1007/jhep08(2022)030
|View full text |Cite
|
Sign up to set email alerts
|

Flavour and dark matter in a scoto/type-II seesaw model

Abstract: The neutrino mass and dark matter (DM) problems are addressed in a Standard Model extension where the type-II seesaw and scotogenic mechanisms coexist. The model features a flavour 𝒵8 discrete symmetry which is broken down to a 𝒵2, stabilising the (scalar or fermion) DM particle. Spontaneous CP violation is implemented through the complex vacuum expectation value of a singlet scalar field, inducing observable CP-violating effects in the lepton sector. The structure of the effective neutrino mass matrix leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 152 publications
0
2
0
Order By: Relevance
“…In this model, the dominance of the tree-level seesaw mechanism over the scotogenic model is a prediction. This is not a generic feature from scoto-seesaw models [7,8,[16][17][18][19][20], it is a result from the fact that the mass mediators for both mechanisms in this model belong to the same…”
Section: A Normal Ordering Of Neutrino Massesmentioning
confidence: 90%
“…In this model, the dominance of the tree-level seesaw mechanism over the scotogenic model is a prediction. This is not a generic feature from scoto-seesaw models [7,8,[16][17][18][19][20], it is a result from the fact that the mass mediators for both mechanisms in this model belong to the same…”
Section: A Normal Ordering Of Neutrino Massesmentioning
confidence: 90%
“…As stated in the next section (for a detailed account, see [1]), neutrino masses are generated by a type-I seesaw and a scotogenic mechanism [5][6][7]. The key feature of this model, in contrast to previous works, is that it naturally predicts the dominance of the seesaw over the scotogenic mechanism [8][9][10][11][12][13][14].…”
Section: The Yukawa Sectormentioning
confidence: 98%
“…-LHC Higgs data: The odd-neutral scalars 𝑆 𝑖 contribute to the Higgs invisible decay through 3For a detailed analysis on the fermion DM scenario see ref. [6]. 4The computation of Ωℎ 2 and 𝜎 SI , is performed with MicrOmegas [21].…”
Section: Dark Mattermentioning
confidence: 99%
“…It can be shown that these LHC Higgs data constraints also exclude the low-mass region 45.6 GeV ≲ 𝑚 𝑆 1 ≲ 60 GeV (see ref. [6] for details). Thus, we conclude that the intermediate mass region 68 GeV ≲ 𝑚 𝑆 1 ≲ 90 GeV for scalar DM is viable since it leads to a correct relic density while evading current collider and DD experimental constraints.…”
Section: Pos(discrete2022)079mentioning
confidence: 99%